A new EWMA median chart with measurement errors in short production runs–An application in yogurt cup filling process. (7th January 2022) - Saha, Sajal; Khoo, Michael B. C.; Abubakar, Sani Salihu; Das, Utpal Kanti; Lee, Ming Ha
Abstract: This article presents an exponentially weighted moving average (EWMA) median chart for short production runs (SPR) (called EWMA SPR median chart). This chart improves the sensitivity of the Shewhart median chart for SPR (called Shewhart SPR median chart) proposed by Khoo et al 15 in the detection of mean shifts. The proposed chart's performance is evaluated by means of the truncated average run length (TARL), truncated standard deviation of the run length (TSDRL), and expected TARL (ETARL) criteria. For all sizes of mean shifts, regardless of the sample size, the findings show that the EWMA SPR median chart outperforms the Shewhart SPR median chart. The EWMA SPR median chart is also investigated when measurement errors are present, as these errors affect the chart's performance. An example is given to illustrate the working of the chart when measurement errors are present.